CAFE ATMOSPHERE AND SERVICE QUALITY ON CONSUMER SATISFACTION - Yudhi Prasetya Mada (International Journal of Innovations in Engineering Research and Technology, 2023)
Marketing has a very important role for the success of entrepreneurs, the main goal of marketing is sales. Sales is a process of exchanging goods or services with a certain amount of value from producers to consumers for the success of a company. Along with the development of technology in the era of globalization, it has brought many changes in terms of lifestyle, behavior and culture in society. Nowadays, very rapid business growth and development requires businesses to compete in marketing the products or services they produce. For this reason, business people can develop the right marketing strategy. A business needs to know their wants and needs regarding products and services, and the most important thing is to be astute in seeing market opportunities.